2015
DOI: 10.1088/0004-637x/805/1/24
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Slow Mode in the Solar Wind and Its Possible Role in Turbulence Dissipation and Ion Heating

Abstract: The solar wind is permeated by various kinds of fluctuations ranging broadly in scales from those of the solar corona and inner heliosphere down to the local ion and electron plasma kinetic scales. The question of what rules the dissipation of magnetohydrodynamic (MHD) turbulence in the solar wind has not conclusively been answered, but remains a key research topic of space plasma physics. Here we propose a new dissipation mechanism, the proton Landau damping of the quasi-perpendicular kinetic slow mode. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…Moreover, even though some points in Fig. 1c and d, may agree better with the curves for IBWs as there is no significant signature in the cross-correlation, this is most likely due to wave-wave interactions between individual KAW packets or KAWs and KSWs (Narita and Motschmann, 2017;Roberts et al, 2017). It is also interesting to note that while the KAW dominates both other wave modes, the majority of the fluctuations do not fall into the thresholds in Table 1.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, even though some points in Fig. 1c and d, may agree better with the curves for IBWs as there is no significant signature in the cross-correlation, this is most likely due to wave-wave interactions between individual KAW packets or KAWs and KSWs (Narita and Motschmann, 2017;Roberts et al, 2017). It is also interesting to note that while the KAW dominates both other wave modes, the majority of the fluctuations do not fall into the thresholds in Table 1.…”
Section: Resultsmentioning
confidence: 70%
“…Several multi-spacecraft observations of the solar wind have revealed that the fluctuations at proton kinetic scales typically have low intrinsic propagation speeds in the plasma frame. This result has been interpreted as evidence of kinetic Alfvén waves (KAWs) (Sahraoui et al, 2010), as coherent structures which are predominantly advected with the bulk velocity (Perrone et al, 2017), as a combination of KAW turbulence and coherent structures (Roberts et al, 2013(Roberts et al, , 2015, or as nonlinear modes where wave-wave interactions have broadened the dispersion relation diagram (Narita and Motschmann, 2017;Roberts et al, 2017). Kinetic slow waves (KSWs) are the kinetic counterpart of the magnetohydrodynamic (MHD) slow mode when it develops a large perpendicular wave number, and it shares many properties with the KAW, such as a similar dispersion relation and anticorrelated fluctuations in magnetic field and density Narita and Marsch, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The observation of pressure-balanced structures (PBSs) in the solar wind (Burlaga & Ogilvie 1970;Vellante & Lazarus 1987;Burlaga et al 1990;Zank et al 1990;Marsch & Tu 1993;Tu & Marsch 1994;Ghosh et al 1998;Bavassano et al 2004;Yao et al 2011Yao et al , 2013aYao et al , 2013bNarita & Marsch 2015) suggests that IA modes indeed account for only a minority of the total compressive energy, because IA waves perturb the total pressure, whereas NP modes are associated with approximate total-pressure balance in the limit   k 0. Future observational studies to constrain the IA fraction in the solar wind will be important for further testing of the importance of the fluctuating-anisotropy effect in the solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…-Kinetic slow mode is a kinetic extension of the MHD slow mode (Zhao et al, 2014;Narita and Marsch, 2015) and its existence is suggested by a pressure-balance structure in the solar wind (Yao et al, 2013). Kinetic slow mode is obtained as a quasi-perpendicular limit of the ion acoustic waves and becomes less damped at highly oblique angles at around 85 • and larger.…”
Section: Introductionmentioning
confidence: 98%
“…There are only few observation cases in space plasmas within a frequency range between the fundamental and several harmonics of the ion gyro-frequency such as fluctuations in the solar wind (Perschke et al, 2013(Perschke et al, , 2014 and in the magnetic reconnection outflow region (Narita et al, 2016a). The ion Bernstein modes are clearly visible in direct numerical simulations, and offer various kinds of wave-wave interactions for the parametric instability (Jenkins et al, 2013).…”
Section: Introductionmentioning
confidence: 99%